A STUDY OF CHILD DELIVERY COMPLICATIONS AMONG PREGNANT WOMEN IN ZAINAB BULKACHUWA WOMEN AND CHILDREN HOSPITAL, GOMBE-NIGERIA - Y. BELLO, HASSANA; ANAS, NASIRU; MAHMUD, BADIYA; Y. BELLO, ABBAYO (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Child delivery complications remain a public health challenge despite several efforts made by government and non-governmental organisations. Socio-cultural, economic and related health care services and logistics remains the most common factors responsible for these complications in Nigeria. This study, therefore, was undertaken to achieve the following objectives; to examine the problems pregnant women face attending antenatal care in Zainab Bulkachuwa Women and Children Hospital and examine the nature of child delivery complications among pregnant women in Zainab Bulkachuwa Women and Children Hospital. Furthermore, the study employed a descriptive research method and data was collected from a sample of 225 pregnant women from the population of 426 registered antenatal women during the study period using Krejcie and Morgan sample size calculator with 5% margin of error and 95% confidence level. The data was analysed using statistical package for the social sciences (version, 21). The findings of the study indicated that, pregnant women face problems such as waiting long time at the hospital and inadequate medical facilities they might needed during antenatal visits among other problems. Furthermore, the study found that, the complications women face includes haemorrhage, spontaneous abortion, obstructed labour, blood transfusion and caesarean section among others. Finally, the study outlines the strategies need to be followed in reducing child delivery complications among pregnant women in the hospital. These include provision of more health care facilities and drugs in the hospital, allowing traditional birth attendants to work in the hospital after training on hygiene and sanitation in and around the labour room and the pregnant woman as well as provision of free health care services to indigent women among others.